REPERTOAR TARI RASJATI SEBAGAI SUMBER GARAP PENYAJIAN TARI - Elma Merdiana dan Lalan Ramlan (Jurnal Seni Makalangan, 2019)
ABSTRAKTari Rasjati dalam genre Jaipongan sebagai sumber garap akan digubah menjadi bentuk penyajiannya yang ”baru”, karena pada tarian ini banyak peluang untuk dikembangkan sesuai kebutuhan, terutama ko-reografi dan pengaturan dinamika irama gerak. Untuk mencapai hasil yang optimal dalam garap penyajian tari Rasjati ini, maka dalam garapan ini menggunakan teori “Gegubahan Tari” dengan pendekatan metode “Gubahan Tari” melalui tahapan penyusunan konsep, proses yang terdiri dari eksplorasi, evaluasi dan komposisi, serta produk akhir yaitu gaya penyajian baru. Adapun hasil yang dicapai dari proses garap penyajian tersebut, adalah tercapainya perwujudan bentuk penyajian yang baru dari sumber repertoar tari Jaipongan dengan tidak merubah identitas repertoar sumbernya.Kata Kunci: Jaipongan, Rasjati, Penyajian Tari. ABSTRACTRepertoar Tari Rasjati As A Source Of Working On Presentation Dance, June 2018. The Rasjati dance in the Jaipongan genre as a source of cultivation will be transformed into a "new" form of presentation, because in this dance there are many opportunities to be developed according to needs, especially choreography and dynamic rhythmic movement settings. To achieve optimal results in working on the Rasjati dance presentation, this work uses the theory of "Gegubahan" with the approach of the "Gubahan Tari" method through the stages of concept preparation, a process consisting of exploration, evaluation and composition, as well as the final product namely presentation style new. The results achieved from the process of working on the presentation, is the achievement of the realization of a new form of presentation from the source of the Jaipongan dance repertoire by not changing the identity of the source's repertoire. Keywords: Jaipongan, Rasjati, Presentation Dance.